Synthesis and Characterization of Hydroxyapatite/TiO2 Coatings on the β-Type Titanium Alloys with Different Sintering Parameters using Sol-Gel Method - Dikici, B.; Niinomi, M.; Topuz, M.; Say, Y.; Aksakal, B.; Yilmazer, H.; Nakai, M. (PLEIADES PUBLISHING LTD, 2018)
In this study, hydroxyapatite (HA) based composite films were successfully syntheses on the beta-type Ti29Nb13Ta4.6Zr (TNTZ). The solutionized TNTZ substrates coated with HA and HA/Titania (TiO2) bioactive composite coatings by sol-gel method under various sintering parameters related to sintering temperatures and heating ramp rates. Microstructural observations of the coatings revealed that apatite was formed on the substrates. The hardness values of the coatings increase with increasing both the sintering temperature and the TiO2 concentration in the coatings layer. However, it was found that the heating ramp rate of the sintering was not affecting the hardness values so much. Also, the hardness values of the HA/TiO2 composite coatings at all sintering temperatures were higher than only HA coated TNTZ samples due to the existence TiO2 phases in the HA matrix. Results indicating that the doping of HA with TiO2, improve the physical consistency between the coating layer and the substrates and provide a better inter-particle bonding due to the existence TiO2 phases in the HA.
Keywords: hydroxyapatite; TNTZ; sol-gel; bioactive coating; sintering; TITANIA/HYDROXYAPATITE COMPOSITE COATINGS; BIOACTIVITY; ANTIBACTERIAL; TEMPERATURE; BEHAVIOR; SURFACE; Metallurgy & Metallurgical Engineering